Antimicrobial Resistance Profiles of Human Commensal Neisseria Species - Maira Goytia; Symone T. Thompson; Skylar V. L. Jordan; Kacey A. King (MDPI AG, 2021)
Pathogenic Neisseria gonorrhoeae causes the sexually transmitted infection gonorrhea. N. gonorrhoeae has evolved high levels of antimicrobial resistance (AR) leading to therapeutic failures even in dual-therapy treatment with azithromycin and ceftriaxone. AR mechanisms can be acquired by genetic transfer from closely related species, such as naturally competent commensal Neisseria species. At present, little is known about the antimicrobial resistance profiles of commensal Neisseria. Here, we characterized the phenotypic resistance profile of four commensal Neisseria species (N. lactamica, N. cinerea, N. mucosa, and N. elongata) against 10 commonly used antibiotics, and compared their profiles to 4 N. gonorrhoeae strains, using disk diffusion and minimal inhibitory concentration assays. Overall, we observed that 3 of the 4 commensals were more resistant to several antibiotics than pathogenic N. gonorrhoeae strains. Next, we compared publicly available protein sequences of known AR genes, including penicillin-binding-protein 2 (PBP2) from commensals and N. gonorrhoeae strains. We found mutations in PBP2 known to confer resistance in N. gonorrhoeae also present in commensal Neisseria sequences. Our results suggest that commensal Neisseria have unexplored antibiotic resistance gene pools that may be exchanged with pathogenic N. gonorrhoeae, possibly impairing drug development and clinical treatment.